Dr. Raúl Reyes — Deep Plane Facelift — Tijuana - Reyes, Raúl (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Raúl Reyes, practicing in Tijuana, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003069; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; tijuana